Evaluation of the Perioperative Period After Off-Pump Coronary Artery Bypass Grafting in Patients with the History of COVID-19 - Artur V. Gabriyelyan; Olexander V. Cheveliuk; Svitlana V. Romanova; Irina V. Kudlai; Marchelina S. Gergi; Svitlana S. Moshta (Ukrainian Journal of Cardiovascular Surgery, 2021)
Previous COVID-19 is known to have negative impact on postoperative course of coronary artery bypass grafting. According to a number of foreign sources, mortality after coronary artery bypass grafting is increased in patients with previous COVID-19, and the perioperative period is accompanied by complications such as myocardial infarction, acute renal failure, acute cerebrovascular accident, sternal infection.The aim. To evaluate the features of the perioperative period after coronary artery bypass grafting in patients with the history of COVID-19.Materials and methods. The research is based on the analysis of data from patients who were operated at the Department of Transplantation and Heart Surgery of Shalimov National Institute of Surgery and Transplantation for the last 2 years. The article presents a comparative analysis of the perioperative period after coronary artery bypass grafting on a beating heart in patients with and without the history of COVID-19. Both groups of patients were basically equivalent in demographics, incidence of comorbidities, NYHA functional class, ejection fraction, and the difference between them was insignificant. Severe course of previous COVID-19 was noted only in 2 (10%) patients, moderate in 6 (30%), mild in 12 (60%). The most common finding was 11% to 30% damage of the lung tissue which was observed in 10 (50%) patients. Residual effects of spiral computed tomography immediately before surgery were detected in 6 (30%) cases.Results and discussion. In the early postoperative period there were such complications as: acute myocardial infarc-tion, acute renal failure, acute cerebrovascular accident, sternal infection. In the early postoperative period, patients in both groups developed complications: 14 (70%) patients in group 1 vs. 7 (35%) patients in group 2. Acute renal failure (ARF) was verified by a 1.5–1.9-fold increase in creatinine levels compared to baseline, or ≥0.3 mg/dL (≥26.5 mmol/l), and was significantly more common in the group of patients after COVID-19 (6 [30%]) than in the group of patients with-out the history of COVID-19 (2 [10%]). The incidence of myocardial infarction confirmed by high levels of highly specific troponin T and changes in electrocardiography also prevailed in group 1 with 4 (20%) patients vs. 2 (10%) patients in group 2 (P <0.001). In patients with a history of COVID-19, the duration of ventilation and the need for additional oxygen-ation was higher compared to those who did not have COVID-19. We found that patients with the history of COVID-19 had more abundant exudates in the first 24 hours: 113 ± 36.4 ml in group 1 vs. 78 ± 26.8 ml in group 2 without COVID-19. The length of stay of the patients in the ICU differs in both groups: 78.4 ± 14.1 hours in group 1 and 52.8 ± 12.1 hours in group 2 (P <0.01), and is observed as a consequence of the above-mentioned complications accompanying early postoperative period.Conclusions. Analysis of the results of coronary artery bypass graft surgery in patients with a history of COVID-19 showed that the postoperative course in them is more severe compared with patients who did not have COVID-19. The patients with the history of COVID-19 who are candidates for coronary artery bypass grafting are more likely to devel-op acute myocardial infarction and acute renal failure manifested by increased creatinine in the postoperative period.